The “tyranny of distance”: community-based veteran suicide prevention in Guam - Sells, Joanna R.; Stearns-Yoder, Kelly A.; Penzenik, Molly E.; Bahraini, Nazanin H.; Sullan, Molly J.; Cruz, Selena; Monteith, Lindsey L.; Brenner, Lisa A. (Frontiers in Public Health, 2025)
The population of Guam is comprised of a high proportion of Asian and/or Pacific Islander individuals, many of whom have served in the military. Minoritized community membership and military service are associated with increased suicide risk. This mixed-methods study was conducted to increase understanding regarding the community context, factors associated with suicide risk among Guamanians, and implementation barriers and facilitators for a community-based suicide prevention program, Together with Veterans (TWV). For this convergent parallel mixed-methods study, data were collected from twelve individuals. Qualitative data were analyzed via a rapid analysis approach. Themes were organized using a socio-ecological model framework, then integrated with quantitative data. Emergent themes by socio-ecological levels included: intrapersonal (e.g., identities, mental health stigma); social-interpersonal (e.g., perceptions of Veterans); social community (e.g., access to care); social organizational (e.g., hope for raising awareness); social public policy (e.g., part of, yet isolated from, the mainland); and chronosystem (i.e., geopolitical history). Quantitative data yielded convergent and divergent findings. Findings highlight unique risk and protective factors faced by those living in Guam, as well as the utility of structured community-based suicide prevention strategies to make change among those living in island communities that are geographically distant from the mainland.